Anatomi Kecemburuan Saudara Kandung: Analisis Psiko-Tafsir Ibn ‘Asyur Terhadap Surah Yusuf Ayat 8 - Sekar Ayu; Agusman Damanik (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the anatomy of sibling jealousy as interpreted by Ibn ‘Asyur in al-Tahrir wa al-Tanwir regarding QS. Yusuf verse 8, and to examine its relevance to sibling jealousy theories in family psychology. This research employs a qualitative approach with a descriptive-analytical library research design. Primary data consist of Ibn ‘Asyur’s interpretation of QS. Yusuf verse 8, while secondary data are drawn from relevant books and recent scholarly articles on sibling jealousy and family psychology. Data were collected through documentation techniques and analyzed using qualitative content analysis. The findings reveal that Ibn ‘Asyur’s interpretation implicitly constructs the anatomy of sibling jealousy through three interconnected psychological layers: perceptual distortion of parental affection, misguided collective pride, and moral justification as a catalyst for destructive action. These findings are consistent with family psychology theories emphasizing the role of perceived differential parental treatment, social identity formation, and the escalation of conflict driven by collective rationalization. This study demonstrates that Ibn ‘Asyur’s interpretation holds significant relevance to contemporary family psychology concepts, affirming that the Qur’an contains profound psychological insights into human emotional dynamics within the family context.